Living wages and the welfare state : the Anglo-American social model in transition / Shaun Wilson. - Wilson, Shaun, 1971- (Policy Press, 2021)
Addressing the rapidly shifting politics of the minimum wage in six English-speaking countries, Shaun Wilson analyses minimum wage policies within a political-economy narrative. Topical and poignant, this book identifies the success of living wage campaigns as central to both welfare state change and alternatives to the Basic Income.